Charged hydrophilic polymer brushes and their relevance for understanding marine biofouling. Issue 6 (2nd July 2016) - Yandi, Wetra; Mieszkin, Sophie; di Fino, Alessio; Martin-Tanchereau, Pierre; Callow, Maureen E.; Callow, James A.; Tyson, Lyndsey; Clare, Anthony S.; Ederth, Thomas
Abstract: The resistance of charged polymers to biofouling was investigated by subjecting cationic (PDMAEMA), anionic (PSPMA), neutral (PHEMA- co -PEG10 MA), and zwitterionic (PSBMA) brushes to assays testing protein adsorption; attachment of the marine bacterium Cobetia marina ; settlement and adhesion strength of zoospores of the green alga Ulva linza ; settlement of barnacle ( Balanus amphitrite and B. improvisus ) cypris larvae; and field immersion tests. Several results go beyond the expected dependence on direct electrostatic attraction; PSPMA showed good resistance towards attachment of C. marina, low settlement and adhesion of U. linza zoospores, and significantly lower biofouling than on PHEMA- co -PEG10 MA or PSBMA after a field test for one week. PDMAEMA showed potential as a contact-active anti-algal coating due to its capacity to damage attached spores. However, after field testing for eight weeks, there were no significant differences in biofouling coverage among the surfaces. While charged polymers are unsuitable as antifouling coatings in the natural environment, they provide valuable insights into fouling processes, and are relevant for studies due to charging of nominally neutral surfaces.